Питомник: роман / Полина Дашкова - Дашкова Полина Викторовна (Серия "Полина Дашкова - лучшая среди лучших", 2020)
Экземпляры: (20210713) / Инвентарный номер: 41712 / Цена: 205.81 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Д 21 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6